2009
DOI: 10.1086/605579
|View full text |Cite
|
Sign up to set email alerts
|

Serum (1→3) β‐d‐Glucan as a Noninvasive Adjunct Marker for the Diagnosis ofPneumocystisPneumonia in Patients with AIDS

Abstract: High serum (1-->3) beta-D-glucan levels are described in patients with Pneumocystis pneumonia (PCP). We evaluated the diagnostic value of beta-D-glucan in 111 patients with AIDS who had PCP and confirmed its usefulness. However, it does not correlate with disease severity and is not suitable for monitoring response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 9 publications
6
74
1
Order By: Relevance
“…We have also found that the fungus Pneumocystis is a frequent respiratory colonizer in HIVinfected individuals, particularly in those with COPD (34)(35)(36). (1→3)-b-D-glucan (BG) is a component of fungal cell walls that is shed into the blood and can be detected in the serum of patients with fungal pneumonia (37,38). We have recently found detectable BG levels in HIVinfected adult outpatients without pneumonia, and BG levels correlate strongly with airway obstruction, DL CO , echocardiographic pulmonary artery pressures, higher inflammatory cytokines, increased sputum neutrophils, and activated peripheral lymphocytes (39).…”
Section: Fungi As Possible Agents Of Microbial Translocationmentioning
confidence: 99%
“…We have also found that the fungus Pneumocystis is a frequent respiratory colonizer in HIVinfected individuals, particularly in those with COPD (34)(35)(36). (1→3)-b-D-glucan (BG) is a component of fungal cell walls that is shed into the blood and can be detected in the serum of patients with fungal pneumonia (37,38). We have recently found detectable BG levels in HIVinfected adult outpatients without pneumonia, and BG levels correlate strongly with airway obstruction, DL CO , echocardiographic pulmonary artery pressures, higher inflammatory cytokines, increased sputum neutrophils, and activated peripheral lymphocytes (39).…”
Section: Fungi As Possible Agents Of Microbial Translocationmentioning
confidence: 99%
“…Measurement of the fungal cell wall component (1-3) ß-D-glucan (BG) in serum has been used as an adjunctive diagnostic tool for diagnosis of PCP [41][42].…”
Section: Serum (1-3) ß-D-glucanmentioning
confidence: 99%
“…Therefore this test may be used as non invasive test for diagnosis of PcP 49 , 50 . This test may however not correlate with disease severity and should not be used to monitor patients on treatment 87 .…”
Section: Other Testsmentioning
confidence: 99%